The Effect of Arbuscular Mycorrhizal Fungi (AMF) Induction to The Growth and Atsiri Oils Content of Three Types Ginger (Zingiber officinale Rosc.) - Qonita Fathin Azizah; Kacung Hariyono (Jember University Press, 2022)
Ginger (Zingiber officinale Rosc.) is one of the biopharmaca plants that have many beneficial contents. In Indonesia, biopharmaca plant production is currently developing. The development production of ginger must be balanced with the standard quality of the global market. There are many metodh to improve the ginger quality, one of them is Arbuscular Mycorrhizal Fungi (AMF) addition. It’s well recognized that the function of Arbuscular Mycorrhizal Fungi (AMF) in ginger plant is to developed the growth and secondary metabolism like atsiri oils. Mode of action the Arbuscular Mycorrhizal Fungi (AMF) has induced root performance to develop the growth and atsiri oils content of gingers. This study aims to discover the effect of Arbuscular Mycorrhizal Fungi (AMF) on the growth and the content of secondary metabolism especially atsiri oils on three types of ginger. Hopefully, the research of this study would be useful for ginger cultivation. The experimental design in this study was a completely randomized design (CRD) factorial pattern of 3x4 with 3 replications. The treatment in this experiment was a combination of various types of ginger by Arbuscular Mycorrhizal Fungi (AMF) administration. Then the data will be analyzed using variance analysis (ANOVA). If treatments are significantly different, so the difference test will be performed with Duncan's multiple ranges at a 5% confidence level. Based on the results of the study showed that there were a significant interaction between the Fungal Mycorrhizal Arbuskula (AMF) fertilizer dose with type of ginger on the plant height, number of tillers, plant wet weight and plant dry weight with the best combination of treatments obtained on the red ginger types, with a 15 grams dose of Arbuscular Mycorrhizal Fungi (AMF) fertilizer (J2F2). A dose of 15 grams arbuscular mycorrhizal fungi (AMF) significantly affected the Leaf Area Index (LAI), fresh rhizome weight, dry rhizome weight, root length, root volume, and atsiri oils, where giant ginger showed the best growth response.